2020
DOI: 10.1111/grs.12289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LAB inoculant and cellulase on the fermentation quality and chemical composition of forage soybean silage prepared with corn stover

Abstract: The objective of the present study was to evaluate the silage quality of forage soybean‐corn stover silage in the south of China. Forage soybean were combined manually with corn stover by ratios of R1 (25:75), R2 (50:50) and R3 (75:25) in fresh weight (FM) and ensiled in bag silos for 60 days at room temperature (20–25°C). All silages were treated without (control) or with lactic acid bacteria (LAB) inoculant (G, Lactobacillus plantarum and Lactobacillus buchneri, 105 cfu/g, of FM), cellulase (C, 0.02% of FM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…(2019), Cheng et al . (2020) and Martínez et al . (2020) reported improved fibre digestibility of corn silages treated with fibrolytic enzymes.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…(2019), Cheng et al . (2020) and Martínez et al . (2020) reported improved fibre digestibility of corn silages treated with fibrolytic enzymes.…”
Section: Resultsmentioning
confidence: 96%
“…(2017) and Cheng et al . (2020) showed that the addition of enzymes only increased CP content. Microbial inoculants can modify the concentration of DM and CP in silages by improving the fermentation pattern, increasing the production of organic acids and other substances that inhibit the growth of undesirable micro‐organisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to the lower pH in LP-treated silage and the antibacterial ability of BF. NH 3 -N is an important indicator for CP degradation, and its content in well-preserved silage should be lower than 10% total N ( Chen et al, 2020b ; Cheng et al, 2021 ). However, the NH 3 -N content of CK on each harvest day was higher than that level.…”
Section: Resultsmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) have been extensively used in order to inhibit the growth of undesirable microorganisms (Dolenčić Špehar et al, 2020). In addition to microbial control, LAB can also be used to improve the fermentation process in silage, contributing for silage quality (Cheng et al, 2021). Many of LAB are able to produce antimicrobial compounds, such as bacteriocins, that can control the bacterial community during the ensilage process (Contreras-Govea et al, 2011).…”
Section: Discussionmentioning
confidence: 99%